Effects of Teriflunomide on B Cell Subsets in MuSK-Induced Experimental Autoimmune Myasthenia Gravis and Multiple Sclerosis. (18th August 2021) - Yilmaz, Vuslat; Ulusoy, Canan; Hajtovic, Sabastian; Turkoglu, Recai; Kurtuncu, Murat; Tzartos, John; Lazaridis, Konstantinos; Tuzun, Erdem
ABSTRACT: Antigen-specific immune responses are crucially involved in both multiple sclerosis (MS) and myasthenia gravis (MG). Teriflunomide is an immunomodulatory agent approved for treatment of MS through inhibition of lymphocyte proliferation. MG associated with muscle-specific tyrosine kinase (MuSK) antibodies often manifests with a severe disease course, prompting development of effective treatment methods. To evaluate whether teriflunomide treatment may ameliorate MuSK-autoimmunity, experimental autoimmune MG (EAMG) was induced by immunizing C57BL/6 (B6) mice three times with MuSK in complete Freund's adjuvant (CFA) (n = 17). MuSK-immunized mice were treated daily with teriflunomide (n = 8) or PBS (n = 9) starting from the third immunization (week 8) to termination (week 14). Clinical severity of EAMG was monitored. Immunological alterations were evaluated by measurement of anti-MuSK IgG, neuromuscular junction deposits, and flow cytometric analysis of lymph node cells. In MS patients under teriflunomide treatment, the peripheral blood B cell subset profile was analyzed. B6 mice treated with teriflunomide displayed relatively preserved body weight, lower EAMG prevalence, reduced average clinical grades, higher inverted screen scores, diminished anti-MuSK antibody and NMJ deposit levels. Amelioration of EAMG findings was associated with reduced memory B cell ratios in the lymph nodes. Similarly, MS patients under teriflunomide treatment showed reduced memory B cell, plasma cell, and plasmablast ratios. Teriflunomide treatment has effectively ameliorated MuSK-autoimmunity and thus may putatively be used in long-term management of MuSK-MG as an auxiliary treatment method. Teriflunomide appears to exert beneficial effects through inhibition of effector B cells.